COVID-19 vaccine distrust in Colombian university students: Frequency and associated variables - Campo-Arias, Adalberto; Pedrozo-Pupo, John Carlos (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work. The frequency of distrust towards the COVID-19 vaccine varies widely depending on the context, way of measurement, and pandemic stage. However, little information is available about Colombian populations. The study aimed to know the frequency and variables associated with COVID-19 vaccine distrust in students of a Colombian university. Methods. A cross-sectional study was carried out which participated emerging adult students of a Colombian university. Results. A total of 1,136 students between 18 and 29 years (M= 22.0, SD = 3.0); most of participants were female (66.0%), non-health students (82.8%), low-income (79.0%), and residents of urban areas (84.9%). It was frequent low institutional trust (74.8%), low cognitive, social capital (27.9%), low fear of COVID-19 (49.5%), low perceived stress related to COVID-19 (83.5%), and high COVID-19 vaccine distrust (78.9%). Non-health carrier (Adjusted OR = 3.63, 95%CI 2.58-5.10), rural residence (AOR = 1.85, 95%CI 1.13-3.04), low income (AOR = 1.84, 95%CI 1.31-2.57), and perceived stress related to COVID-19 (AOR = 1.74, 95%CI 1.20-2.54) were related to high COVID-19 vaccine distrust. Conclusions. COVID-19 vaccine distrust is high among emerging adult Colombian university students. The COVID-19 vaccine distrust is related to non-health science carriers, rural residents, low-income, and low-perceived stress related to COVID-19. The COVID-19 related health literacy should be improved in students of this university considering socio-cultural background.